Net Geochemical Release of Base Cations From 25 Forested Watersheds in the Catskill Region of New York - Nieman, Sara C.; Johnson, Chris E. (Frontiers in Forests and Global Change, 2021)
Chemical weathering of minerals is the principal mechanism by which base cations (Ca2+, Mg2+, K+, and Na+) are released and acidity is neutralized in soils, bedrock and drainage waters. Quantifying the release of base cations from watershed soils is therefore crucial for the calculation of “critical loads” of atmospheric acidity to forest ecosystems. We used a mass-balance approach to estimate the rate of release of base cations in 25 headwater catchments in the Catskill region of New York, an area historically subject to high inputs of acid deposition. In 2010-2013, total net base cation release via geochemical processes averaged 1704 eq ha-1 yr-1 (range: 928-2622). Calcium accounted for 58% of this total, averaging 498 mol ha-1 yr-1 (range: 209-815). Mass balance estimates of net geochemical release of base cations were most strongly driven by stream export and biomass uptake fluxes, with only minor contributions from precipitation. Documented rates of base cation depletion from soil exchange sites in the region were also small relative to the net geochemical release rates. We observed a significant influence of bedrock type on net base cation release rates (P = 0.002), and a weak but significant negative correlation with watershed elevation (r = -0.51). Relationships with other geographic factors such as aspect and watershed size were not significant. Net base cation release was 4.5 times higher than precipitation inputs of SO42- and NO3-, suggesting that sources of acidity internal to the watershed are now more important drivers of weathering than acid deposition. Our data suggest that release of base cations from most Catskill forest soils is sufficient to neutralize existing inputs of acidity.